2015
DOI: 10.1111/1468-2346.12392
|View full text |Cite
|
Sign up to set email alerts
|

Carl Schmitt in the Kremlin: the Ukraine crisis and the return of geopolitics

Abstract: The protracted crisis in Ukraine has exposed fundamental political differences between leaders in western Europe and their counterparts in Russia. The very existence of the European Union was meant to have refuted geopolitics as a useful theoretical lens through which to view power relations in Europe. After all, the European project is based on the idea that boundaries no longer matter and that national sovereignty is obsolete. And yet, geopolitics remains critically important—certainly for Europe's potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…However, by promoting this claim, they confirm that the events were not understood as a security crisis by the EU. Instead, as Realists also stress, the crisis represented a clash of worldviews between Russia and the EU (Auer, ; Mearsheimer, ; Rynning, ). As Auer argues, ‘In order to challenge Putin's Russia effectively, I argue, Europe and Germany should indeed reclaim geopolitics for their own purposes’ (Auer, , p. 958).…”
Section: The Limited Role Of Coercionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by promoting this claim, they confirm that the events were not understood as a security crisis by the EU. Instead, as Realists also stress, the crisis represented a clash of worldviews between Russia and the EU (Auer, ; Mearsheimer, ; Rynning, ). As Auer argues, ‘In order to challenge Putin's Russia effectively, I argue, Europe and Germany should indeed reclaim geopolitics for their own purposes’ (Auer, , p. 958).…”
Section: The Limited Role Of Coercionmentioning
confidence: 99%
“…It has been suggested that the Union underestimated Russian security concerns and failed to consider that offering an association agreement to Ukraine might be seen as an infringement on Russia's sphere of influence (Kissinger, ; MacFarlane and Menon, ; Mearsheimer, ; Sakwa, ). Such criticisms are frequently accompanied by suggestions that in response to Russian aggression, the EU and ‘the West’ need to return to a foreign policy inspired by a logic of geopolitics and take into account what the authors consider ‘the realities of power’ (Auer, ; Mearsheimer, ; Rynning, ; Sakwa, ).…”
Section: The Approachmentioning
confidence: 99%
“…A stream of recent publications and conference papers focusing on the EU's ‘actorness’ in response to the Russian aggression in Ukraine reinforces this narrative. Matthijs and Kelemen (, p. 100), in a tellingly‐titled article ‘Europe Reborn’, observe that ‘a resurgent Russia on Europe's doorstep has finally spurred the EU to action’. Auer () advocates that the EU adopts ‘muscular liberalism’ to more effectively confront Russia.…”
Section: Competing Narratives Of the Conflictmentioning
confidence: 99%
“…Matthijs and Kelemen (, p. 100), in a tellingly‐titled article ‘Europe Reborn’, observe that ‘a resurgent Russia on Europe's doorstep has finally spurred the EU to action’. Auer () advocates that the EU adopts ‘muscular liberalism’ to more effectively confront Russia. Howorth and Menon () urge EU Member States to ‘wake up’ by overcoming their anachronistic commitment to sovereignty and grasping the reality that only when unified, the EU can stand for its interests effectively.…”
Section: Competing Narratives Of the Conflictmentioning
confidence: 99%
“…However, it appears that this pledge only emboldened Russia: 'the Russian government perceived it as a sign of weakness, an open invitation for its own military solution' (Auer, 2015). Germany (backed by France) was instrumental in fostering ceasefire and peace negotiations between Ukraine and Russia, leading to the two Minsk agreements on resolving the tensions in Eastern Donbass.…”
Section: Russia's Geopolitical Contestationmentioning
confidence: 99%